High-Dose Dual Therapy Versus Bismuth-Containing Quadruple Therapy for the Treatment of Helicobacter pylori Infection: A Systematic Review with Meta-Analysis - Yin, Zhikun; Li, Ji; Huang, Weifeng; Lei, Xiaoyi; Xu, Dong; Xu, Guihua; Li, Hua; Zhang, Jinyan (Turkish Journal of Gastroenterology, 2022)
Background: This study aimed to evaluate the efficacy and safety of high-dose dual therapy for Helicobacter pylori (H. pylori) eradication compared to bismuth-containing quadruple therapy. Methods: The electronic database of PubMed, Embase, and Cochrane Library were searched from inception to March 18, 2021. Randomized, controlled trials that evaluated high-dose dual therapy versus bismuth-containing quadruple therapy for H. pylori infection were included. Results: We included 6 studies containing 1677 patients with H. pylori infection. This meta-analysis demonstrated that high-dose dual therapy achieved similar eradication rate compared with bismuth-containing quadruple therapy (intention-to-treat: 84.6% vs 83.7%, relative risk (RR) = 1.01, 95% CI: 0.97-1.06, P = .49; per-protocol = 88.4% vs 89.0%, RR = 1.00, 95% CI: 0.97-1.04, P = .99). However, highdose dual therapy showed fewer side effects (13.1% vs 32.0%, RR = 0.51, 95% CI: 0.34-0.78, P = .002) and better compliance (96.1% vs 93.3%, RR = 1.03, 95% CI: 1.00-1.05, P = .03) compared to bismuth-containing quadruple therapy. Conclusion: This meta-analysis demonstrated that high-dose dual therapy is equally effective with bismuth-containing quadruple therapy in eradicating H. pylori, with fewer side effects and better compliance.